Energy dissipation of MMC‐HVDC based onshore wind power integration system with FB‐DBS and DCCB. Issue 2 (6th December 2019) - Cao, Shuai; Xiang, Wang; Lu, Xiaojun; Lin, Weixing; Zhang, Kai; Wen, Jinyu; Zhang, Xin
Abstract : With the development of high‐voltage direct current (HVDC), modular multilevel converter (MMC) is seeking its application in onshore wind power integration. AC and DC faults are important issues for the wind power integration system, during which the wind generation system continuously provides wind power and the surplus power may cause overvoltage to sub‐modules of MMC. This study focuses on the energy dissipation during AC and DC faults for the overhead‐line MMC‐HVDC system integrating large‐scale wind power. A two‐terminal MMC‐HVDC system with permanent magnet synchronous generator based wind farm is studied. Hybrid DC circuit breakers (DCCBs) are employed to interrupt DC fault current and the method based on measuring the rate of change of DC line voltage is adopted to trip DCCBs. Also a full‐bridge sub‐module based dynamic braking system (FB‐DBS) is implemented at the DC link to absorb the surplus wind power in case of AC or DC faults in the HVDC grid. To ride‐through AC and DC faults without blocking IGBTs, the control of hybrid DCCB and the system fault ride‐through strategies are properly designed. PSCAD/EMTDC simulations are shown to demonstrate theoretical analysis.